Persistence of seed-based activity following segmentation of a microRNA guide strand - Chorn, Guillaume (Cold Spring Harbor Laboratory Press, 2010)
microRNAs are ∼22 nucleotide regulatory RNAs that are processed into duplexes from hairpin structures and incorporated into Argonaute proteins. Here, we show that a nick in the middle of the guide strand of an miRNA sequence allows for seed-based targeting characteristic of miRNA activity. Insertion of an inverted abasic, a dye, or a small gap between the two segments still permits target knockdown. While activity from the seed region of the segmented miRNA is apparent, activity from the 3′ half of the guide strand is impaired, suggesting that an intact guide backbone is required for contribution from the 3′ half. miRNA activity was also observed following nicking of a miRNA precursor. These results illustrate a structural flexibility in miRNA duplexes and may have applications in the design of miRNA mimetics.